Evaluation of laminate veneer preparation depth with 3D systems - ÖZKAN, YASEMİN; ASLAN, YILMAZ UMUT (My University, 2020)
Background: Preparation depth of laminate veneers are essential inretention and structural integrity of restorations. The aim of this studywas to evaluate the difference between a trained professionalprosthodontist (PP) and a postgraduate prosthodontics student (PPS)in the preparation depth of laminate veneers by scanning the toothwith a 3D scanner before and after the preparation.Methods: Twenty extracted human maxillary central incisors wereevaluated by a PP and PPS. A 0.5 mm depth guide bur was used infor facial reduction and a 1 mm incisal reduction was performed witha deep chamfer. The teeth were scanned with a laser scanner at anaccuracy of 10 µm. The teeth were separated into 3 parts (incisal,middle and cervical) and then 5 points were randomly selected on theunprepared tooth and then lapped over when the preparation hadbeen completed. The data of the difference was calculated in 3Dscanning software Magics (Materialise NV, Belgium). Statisticalanalysis were performed with one-way ANOVA (p < 0.05).Results: PP results showed mean values in the Incisal of0.328+0.045 mm, Middle of 0.375+0.097 mm and Cervical of0.471+0.07 mm. PPS results showed mean values in the Incisal of0.323+0.056 mm, Middle results of 0.403+0.083 mm and Cervicalresults of 0.462+0.075 mm.Conclusion: These results suggest that a PP or a PPS can bothachieve the same precision in the preparation using a depth guidebur.

Amaç: Lamina veneer restorasyonlarında preparasyon derinliği,_x000D_ yapısal sağlamlığın ve tutuculuğun sağlanmasında temel_x000D_ faktörlerin başında gelir. Bu çalışmanın amacı, deneyimli bir_x000D_ prostodontist (PP) ve yüksek lisans protodonti öğrencisinin_x000D_ (PPS) lamina preparasyon derinliklerinin, preparasyon_x000D_ öncesinde ve sonrasında 3B tarayıcı ile farklılıklarının_x000D_ değerlendirilmesidir._x000D_ Gereç ve yöntemler: PP ve PPS 20 adet çekilmiş insan_x000D_ maksiller santral kesiciyi değerlendirmiştir. Fasiyel preparasyon_x000D_ için 0,5 mm’lik derinlik rehberli frez kullanılmıştır. İnsizal_x000D_ preparasyon için ise 1 mm’lik champher frez kullanılmıştır._x000D_ Dişler, 10 µm hassasiyetinde lazer tarayıcı ile taranmıştır. Dişler_x000D_ 3 kısıma (insizal, orta ve servikal) bölünmüş ve 5 noktadan_x000D_ incelenmiştir. Preparasyon yapılmamış ve yapılmış dişler üst_x000D_ üste çakıştırılarak Magics (Materialise NV, Belgium) 3B tarama_x000D_ yazılımında aralarındaki farklar incelenmiştir. İstatistiksel analiz_x000D_ tek yünlü ANOVA ile yapılmıştır (p < 0.05)._x000D_ Bulgular: PP sonuçları ortalama insizalde 0.328+0.045 mm,_x000D_ ortada 0.375+0.097 mm, servikalde ise 0.471+0.07 mm_x000D_ olurken, PPS sonuçları ortalama insizalde 0.323+0.056 mm,_x000D_ ortada 0.403+0.083 mm ve servikalde 0.462+0.075 mm olarak_x000D_ bulunmuştur._x000D_ Sonuç: Bu sonuçlar, derinlik belirleyici frez kullanıldığında PP ve_x000D_ PPS benzer preparasyon hassasiyet gösterdiğini belirtmektedir.
Lamina veneer preparasyon derinliklerinin 3B sistemler ile değerlendirilmes